1998
DOI: 10.1097/00004872-199816110-00004
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in home and ambulatory blood pressure in the PAMELA population

Abstract: Seasonal influences on blood pressure are not limited to conventional measurements but characterize daily values as well. These effects are visible in both normal and elevated blood pressure values, regardless of the effect of antihypertensive drugs. This has implications both for the clinician and for studies aimed at evaluating the effects of antihypertensive treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
101
1
14

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 191 publications
(122 citation statements)
references
References 17 publications
6
101
1
14
Order By: Relevance
“…Second, previous studies have examined the association between cold temperature and BP levels and BP variability by assessing their absolute levels. 13,15,16 In contrast, the study by Murakami et al has revealed an association between the difference in outdoor temperature between the coldest and warmest days and the difference of prewaking morning BP increase between the coldest and warmest days. This point deserves to be mentioned, because a recent study demonstrated that an increased risk for CVDs in association with cold temperature was more relevant in the context of an unexpected temperature decrease than in terms of the absolute temperature level itself.…”
mentioning
confidence: 84%
See 3 more Smart Citations
“…Second, previous studies have examined the association between cold temperature and BP levels and BP variability by assessing their absolute levels. 13,15,16 In contrast, the study by Murakami et al has revealed an association between the difference in outdoor temperature between the coldest and warmest days and the difference of prewaking morning BP increase between the coldest and warmest days. This point deserves to be mentioned, because a recent study demonstrated that an increased risk for CVDs in association with cold temperature was more relevant in the context of an unexpected temperature decrease than in terms of the absolute temperature level itself.…”
mentioning
confidence: 84%
“…1,12,13 Several studies have demonstrated that BP is subject to seasonal influences and is lower in hot than in cold months. [13][14][15] This influence is not limited to office measurements but affects daily values (that is, home BP and ambulatory BP) as well. 15 Moreover, Modesti et al 16 recently examined the association between air temperature and ambulatory BP profile: they showed that cold temperature was significantly associated with excessive sleep-through MS in elderly persons, even when they were treated with a higher number of antihypertensive drugs in cold weather.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7] However, in these large studies the seasonal effects were small. Summerwinter differences for SBP ranged from 2 to 7 mm Hg and for DBP from 0.3 to 5 mm Hg under the condition of recumbency, sitting, standing, or 24-h ambulatory monitoring.…”
Section: Introductionmentioning
confidence: 99%